Development of 3-Dimensional Cartoon Animation Videos to Improve Higher Order Thinking Skills of Elementary School Students - Zaka Hadikusuma Ramadan; Mitha Dwi Anggriani; Febrina Dafit (Postgraduate, University of Mataram, 2023)
This research aims to develop 3-dimensional cartoon animation video media to improve the Higher Order Thinking Skills (HOTS) of fourth grade elementary school students. This research uses an R&D method that adopts the ADDIE model with five stages, namely (Analysis, Design, Development, Implementation and Evaluation). The data collection instruments used were questionnaires given to design validators, material validators, language validators for feasibility, teacher and student responses to test practicality and tests to test the effect of 3-dimensional cartoon animation video media on students' Higher Order Thinking Skills (HOTS). The results of this research produced a 3-dimensional cartoon animated video media product that can be used at the elementary school level as a learning medium that meets the very appropriate criteria with an average score of 92.65% from the design validator, 92.19% for the material and 88 for the language validator. 75%. The response given by educators was 92.5% in the very interesting category and small-scale trials carried out by students received a score of 93.33% in the very interesting category. Video media is also able to increase the Higher Order Thinking Skills (HOTS) of fourth grade elementary school students based on product effectiveness test results by obtaining a significance value of 0.00 < 0.05.